Leveraging Technology to Improve Learning Independence in Chemistry: A Study on Moodle Integration - Nur Lailatul Fitriyah Abidin; Kusumawati Dwiningsih; Phaosan Jehwae; Christina Kartika Sari (Universitas Muhammadiyah Surakarta, 2024)
This study addresses the issues of the low level of learning independence of students, especially in understanding abstract chemical materials such as chemical bonds, as well as limited learning time, which often results in suboptimal comprehension and the omission of some sub-materials. In addition, the use of media in the learning process rarely incorporates technological advancements. This study aims to determine if a website integrated with Moodle can enhance the learning independence of students in chemical bonding material. This study employed the research and development method using the 4D model, which comprises four stages. However, this study only included three stages, namely define, design, and develop. The target population consisted of 29 eleventh-grade high school students. The instruments used to collect data were validation sheets, an independence questionnaire, and pretest-posttest assessments. The feasibility of the integrated chemistry learning website with Moodle was evaluated through validity and effectiveness tests. The validity test involved three validators, consisting of two lecturers and one teacher. Meanwhile, the effectiveness was analyzed using the n-gain from the results of the independence questionnaire and pretest-posttest assessments. The results of this study indicated that the chemistry learning website integrated with Moodle significantly enhanced the learning independence of students with the validation results of 5 for content validity and 4 for construct validity, while the n-gain results from the independence questionnaire and pretest-posttest assessments fall into the high category. In conclusion, this media effectively promoted independence across five indicators of learning independence.